Applications of Carbon Nanotubes in the Field of Biomedicine - Wang, Youwen (Exploring Science Academic Conference Series, 2026)
Carbon nanotubes, with their excellent mechanical, optical, and thermal properties as well as good biocompatibility, show broad application prospects in the field of biomedicine. This article systematically reviews its research progress in the fields of gene and drug delivery, biomedical imaging, cancer radiotherapy, and combined drug -photothermal therapy, with a focus on analyzing the innovative breakthroughs and existing challenges of core technologies such as targeted delivery, stimulus -responsive release, integrated diagnosis and treatment, and radiotherapy sensitization. Research shows that surface - modified carbon nanotubes can achieve targeted delivery and intelligent release of drugs and genes. Their optical and magnetic properties support integrated multimodal diagnosis and therapy. As radiotherapy sensitizers, they can enhance radiation energy deposition, and combined treatments can improve anticancer effects and reduce toxic side effects. Currently, there are still bottlenecks in its biosafety, large -scale production, and clinical translation. In the future, it is necessary to advance its clinical application in the biomedical field through material optimization, precise functional regulation, and the improvement of safety evaluation systems.